Menjadi Gereja yang Membina: Tanggung Jawab Spiritual dalam Pertumbuhan Jemaat - Surudiaman Lase; Riste Tioma Silean (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The church is not merely a place of worship; it is a community of believers who share a divine responsibility to help one another grow spiritually. In Indonesia, a nation rich in religious and cultural diversity, the church can serve as a strategic agent of both spiritual and social transformation. This paper explores the church’s holistic responsibility in fostering the spiritual growth of its members through intentional discipleship, character formation, biblical teaching, and mission-oriented leadership. Emphasis is placed on the importance of building a contextual and transformative discipleship model, especially in addressing current social challenges, particularly those related to the younger generation. A nurturing church will encourage its members to embody the values of Christ, becoming agents of change, sources of hope, and witnesses of God’s love among others. By fulfilling this calling, the church makes the Kingdom of God present in the world.